2005
DOI: 10.1016/j.icarus.2004.10.023
|View full text |Cite
|
Sign up to set email alerts
|

The atmospheric circulation and dust activity in different orbital epochs on Mars

Abstract: A general circulation model is used to evaluate changes to the circulation and dust transport in the martian atmosphere for a range of past orbital conditions. A dust transport scheme, including parameterized dust lifting, is incorporated within the model to enable passive or radiatively active dust transport. The focus is on changes which relate to surface features, as these may potentially be verified by observations. Obliquity variations have the largest impact, as they affect the latitudinal distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 37 publications
10
97
0
Order By: Relevance
“…Kahre et al (2006) estimated that dust devils contribute 50% of the annual atmospheric dust loading during a year without a global-scale dust storm. This is broadly consistent with figures published in Newman et al (2005) for the present orbital epoch, who show the total amount of dust lifted from the surface by each mechanism. Also, this fits with the observational estimates on the annual dust devil flux mentioned in Section 4.1 (Whelley and Greeley 2008;Cantor et al 2006).…”
Section: Dust Devils Are a Larger Component Of The Dust Cycle On Marssupporting
confidence: 92%
See 1 more Smart Citation
“…Kahre et al (2006) estimated that dust devils contribute 50% of the annual atmospheric dust loading during a year without a global-scale dust storm. This is broadly consistent with figures published in Newman et al (2005) for the present orbital epoch, who show the total amount of dust lifted from the surface by each mechanism. Also, this fits with the observational estimates on the annual dust devil flux mentioned in Section 4.1 (Whelley and Greeley 2008;Cantor et al 2006).…”
Section: Dust Devils Are a Larger Component Of The Dust Cycle On Marssupporting
confidence: 92%
“…Newman et al 2002a,b;Basu et al 2004;Kahre et al 2006;Mulholland et al 2013;Newman and Richardson 2015). In these models the dust devils parameterization contributes up to one half of the total annual dust budget (Newman et al 2005;Kahre et al 2006). Such lifting tends to peak around both solstices in the summer hemisphere, though with greater lifting in the southern hemisphere during summer.…”
Section: Marsmentioning
confidence: 99%
“…The dependence of the threshold velocity on near-surface atmospheric density (∼ ρ −1/2 ) means that this is referred to as a constant threshold stress approach, since surface stress ζ is defined as ζ = ρu * 2 . This is the method that was used by Newman et al (2005), and in other more recent studies. The threshold calculation did not include any modification due to a non-negligible surface roughness length (maps of which have recently become available).…”
Section: Wind Stress Lifting With Constant Threshold Stressmentioning
confidence: 99%
“…Several studies have suggested how the quasi-periodic variations of the orbital parameters have affected martian climate over time and discussed how the polar deposition rates of ice and dust may have varied accordingly (Toon et al, 1980;Cutts and Lewis, 1982;Laskar et al, 2002;Levrard et al, 2007;Newman et al, 2005). However, while the insolation influence of climate and depositional processes appears inevitable, it has remained unclear whether the climate signal recorded in the stratigraphy can be interpreted and linked to variations of insolation.…”
Section: Introductionmentioning
confidence: 99%